Improvement Effect of Mitotherapy on the Cognitive Ability of Alzheimer's Disease through NAD+/SIRT1-Mediated Autophagy - Xiaoxi Yang; Peiyu Zhou; Zizhen Zhao; Jingli Li; Zhigang Fan; Xiaorong Li; Zhihong Cui; Ailing Fu (MDPI AG, 2023)
To date, Alzheimer's disease (AD) has grown to be a predominant health challenge that disturbs the elderly population. Studies have shown that mitochondrial dysfunction is one of the most significant features of AD. Transplantation therapy of healthy mitochondria (mitotherapy), as a novel therapeutic strategy to restore mitochondrial function, is proposed to treat the mitochondria−associated disease. Also, the molecular mechanism of mitotherapy remains unclear. Here, we applied the mitotherapy in AD model mice induced by amyloid−β (Aβ) plaque deposition and suggested that autophagy would be an important mechanism of the mitotherapy. After the healthy mitochondria entered the defective neuronal cells damaged by the misfolded Aβ protein, autophagy was activated through the NAD+−dependent deacetylase sirtuin 1 (SIRT1) signal. The damaged mitochondria and Aβ protein were eliminated by autophagy, which could also decrease the content of radical oxygen species (ROS). Moreover, the levels of brain−derived neurotrophic factor (BDNF) and extracellular−regulated protein kinases (ERK) phosphorylation increased after mitotherapy, which would be beneficial to repair neuronal function. As a result, the cognitive ability of AD animals was ameliorated in a water maze test after the healthy mitochondria were administrated to the mice. The study indicated that mitotherapy would be an effective approach to AD treatment through the mechanism of autophagy activation.